International Conference on Transportation and Development 2020 Highway and Airfield Pavements - Zhang (American Society of Civil Engineers, 2020)
This collection contains 28 peer-reviewed papers on highway and airfield pavements presented at the International Conference on Transportation and Development 2020, held in Seattle, Washington, May 26-29, 2020.
Title from content provider.
Keywords: Transportation.; elektronické knihy; electronic books